Role of Slag Replacement on Strength Enhancement of One-Part High-Calcium Fly Ash Geopolymer - Intarabut, Darrakorn; Sukontasukkul, Piti; Phoo-ngernkham, Tanakorn; Hanjitsuwan, Sakonwan; Sata, Vanchai; Chumpol, Poopatai; Sae-Long, Worathep; Zhang, Hexin; Chindaprasirt, Prinya (Civil Engineering Journal, 2024)
This paper reports the effect of slag (SL) replacement and water-to-binder (w/b) ratio on properties of one-part geopolymer derived from high-calcium fly ash (FA) and sodium silicate powder (NP). The FA was replaced by SL at the rates of 20% and 40%, respectively. This study focused on conducting experimental tests to evaluate the relative slump, setting time, compressive strength, and flexural strength of one-part FA-based geopolymer. The relationship between compressive and flexural strengths of one-part geopolymer mortar was expressed using the simplified linear regression model, whereas the normalization of compressive and flexural strengths with SL replacement by the strength of one-part geopolymer mortar without SL as the divisor was also evaluated. Experimental results showed that the increase of SL replacement and w/b ratio significantly affected the workability and strength development of one-part geopolymer mortar. Higher SL replacement exhibited a positive effect on their compressive and flexural strengths; however, a reduction in its setting time was obtained. The enhancement in strength development of one-part geopolymer was primarily due to the increased calcium content of SL. Similarly, reducing the w/b ratio in the production of one-part geopolymer resulted in a decrease in setting time and an increase in strength development. Based on the relationship between compressive and flexural strengths, the prediction coefficient value (R2) obtained from the curve fitting procedure was 0.835, indicating a good level of reliability and acceptability for engineering applications. Doi: 10.28991/CEJ-SP2024-010-013 Full Text: PDF